Neuromyelitis optica and liver cirrhosis: an association or co-incidence - Kumar, Arjun; Das, Ananya; Agarwal, Mayank; Raina, Rohit; Kant, Ravi (International Journal of Research in Medical Sciences, 2023)
Neuromyelitis optica (NMO) is a rare central nervous system demyelination syndrome predominantly targeting optic nerves and the spinal cord. Here we present a middle-aged female presenting with new onset quadriparesis and a history of persistent splenomegaly and pancytopenia, eventually being diagnosed as NMO along with autoimmune cirrhosis. The association of NMO spectrum disorders (NMOSD) with chronic liver disease has not been previously described in the literature. The purpose of this case report is to bring forward an unusual presentation and to ascertain whether it could be part of a heterogenous spectrum of an autoimmune disorder, or merely a co-incidence.